Resolving the structure of the Galactic foreground using Herschel measurements and the Kriging technique. Issue Volume 12:Issue S333(2017) (8th May 2018) - Pinter, S.; Bagoly, Z.; Balázs, L. G.; Horvath, I.; Racz, I. I.; Zahorecz, S.; Tóth, L. V.
Abstract: Investigating the distant extragalactic Universe requires a subtraction of the Galactic foreground. One of the major difficulties deriving the fine structure of the galactic foreground is the embedded foreground and background point sources appearing in the given fields. It is especially so in the infrared. We report our study subtracting point sources from Herschel images with Kriging, an interpolation method where the interpolated values are modelled by a Gaussian process governed by prior covariances. Using the Kriging method on Herschel multi-wavelength observations the structure of the Galactic foreground can be studied with much higher resolution than previously, leading to a better foreground subtraction at the end.